Maize (Zea mays L.) genome size indicated by 180-bp knob abundance is associated with flowering time - Yinqiao Jian (Nature Portfolio, 2017)
Abstract Flowering time is considered one of the most important agronomic traits in maize (Zea mays L.), and previous studies have indicated that this trait is correlated with genome size. We observed a significant difference in genome size between tropical and temperate inbred lines and a moderate positive correlation between genome size and 180-bp knob abundance determined by high-throughput sequencing in maize inbred lines in this study. We assembled the reads that were mapped to 180-bp knob sequences and found that the top ten abundant 180-bp knob sequences are highly variable. Moreover, our results indicate that genome size is associated with the flowering time of both male and female flowers, in both tropical and temperate inbred lines and under both tropical and temperate environments. To identify loci associated with genome size, we performed a genome-wide association study. The analysis identified three genomic regions associated with genome size, of which two were novel while the third one is located close to the known knobs K8L1 and K8L2. Overall, our results indicate that selection for breeding materials with earlier flowering times can be assisted by choosing germplasms with smaller genome sizes and that genome size can be determined based on the abundance of 180-bp knobs.